PENGARUH TYPE THINK PAIR SHERE TERHADAP HASIL BELAJAR IPA SDN 39 PONTIANAK KOTA - Anggraini, Niki (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract Â From the results of observation and interview, the process of learning Natural Science is still monotonous and does not involve students actively, so that student learning outcomes are still below the KKM. Because it is done by using cooperative learning Type Think Pair Shere Cooperative so that students get better learning outcomes.The research method used is a quasi experiment with the research design used is Nonequivalent Control Group Design. The sample of this research is 60 students. File collection technique is the measurement and direct observation. The file collecting tool used is the observation sheet and multiple choice test questions amounted to 30 questions. From the pretest results obtained the average value obtained in the control class is 46.76. While the experimental class is only 51.51 and categorized as low. While the average post test result after treatment was 61.17 in the control class and 82.42 in the experimental class. This shows the results of student learning by applying the model of cooperative learning type Think Pair Share achieve mastery learning. From result of t-test analysis t obtained equal to 3,15 and t table = 2,005. This means 3.15> 2.005, then t count> t table, it can be said Ho rejected and Ha accepted. So it is concluded that there is influence of using Think Pair Shere Type to learning result of science class V SDN 39 Pontianak Kota. Â Keywords: Influence, Think Pair Share, learning outcomes Â